Menopause guideline appraisal and algorithm development for premature ovarian insufficiency. (December 2019) - Yeganeh, Ladan; Boyle, Jacqueline A.; Wood, Anna; Teede, Helena; Vincent, Amanda J.
Highlights: Significant limitations were identified in the quality of menopause guidelines. Menopause guidelines vary in regard to content and details of recommendations. Consensus was observed between high scoring guidelines for some EM/POI recommendations. Abstract: Objectives: Clinical practice guidelines (CPGs) are systematically developed statements that guide clinicians to provide appropriate healthcare. The aims of this study were: 1) to systematically evaluate the quality of menopause management CPGs; 2) to identify menopause topics included in the CPGs; 3) to summarize the recommendations regarding either early menopause (EM) or premature ovarian insufficiency (POI) provided by high-scoring CPGs; and 4) to develop EM/POI management algorithms. Study design: A systematic search for CPGs published between 2012 and 2017 was conducted using Medline, Embase, All EBM, CPG databases and medical websites. Appraisal was conducted by 4 independent reviewers using the Appraisal of Guidelines for Research & Evaluation II instrument (AGREE II). Inter-rater reliability was calculated using the intraclass correlation coefficient. Recommendations regarding EM/POI were extracted from high-scoring CPGs and translated into a management algorithm, which was refined on the basis of feedback from expert clinicians. Results: The systematic search yielded 22 CPGs for review. Only 2 were assessed as high quality, with 10 average and 10 considered low quality. Scope and purpose (73% ± 15%) and clarity of presentation (78% ± 15%) achieved the highest mean scores, while applicability scored the lowest (23% ± 18%). Inter-rater agreement was 0.74 (good) to 0.91 (very good). The most comprehensive CPGs were those developed by the National Institute for Health and Care Excellence (NICE), the International Menopause Society (IMS) and the European Menopause and Andropause Society (EMAS). Conclusions: Most menopause CPGs are poor to average quality and there is variation between them in EM/POI management recommendations. EM/POI management algorithms were developed from high-scoring CPGs.